Synthesis of Cocoamide Dea Surfactant From Virgin Coconut Oil (VCO) Through Ester Aminolysis Using Microwave - Lailatul Qadariyah; Achmad Rifky; Rahmadi Arnoesaga R. (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2025)
The aim of this research is to find the optimum operating conditions in the aminolysis process of methyl ester into surfactant with variable of microwave power, heating time, and reactant weight ratio. Transesterification is a reaction that removes alcohol and forms esters and other forms of alcohol. In the transesterification, VCO was mixed methanol with mol ratio of 1:6 and NaOH catalyst as much as 0.6% by weight of oil was added. The reaction was carried out for 3 minutes and the microwave power was 450 W while stirring with a magnetic stirrer. After that, the ester aminolysis step was carried out by mixing the methyl ester from the transesterification step with diethanolamine in the microwave power range of 150-750 W, reaction time range of 0-30 minutes, and reactant weigt ratio range of 1-2. Cocoamidea DEA will be analyzed using FT-IR spectrophotometry, acid number, saponification number, ester number, and also HLB. The highest yield of Cocomide DEA and surfactant conversion were 87.47% and 0.83 at reaction time of 20 minutes, microwave power of 600 W, and ratio of weight of methyl reactant 1:2. Cocoamide DEA compounds have been formed with the emergence of amide groups, namely C=O with a wavenumber of 1619.75 cm-1. The surfactant value of HLB is 6-8 which corresponds to its function as a water in oil emulsifier.